Cisternostomy in Traumatic Brain Injury for a Novel Approach to Treatment: Review of Current Status - Agrawal, Manish; Mishra, Keshav; Babal, Rohit; Purohit, Devendra (Indian Journal of Neurotrauma, 2021)
Cisternostomy (CS) is a recently introduced procedure to mitigate the cerebrospinal fluid shift edema and secondary injury in traumatic brain injury patients. There have been numerous reports describing its efficacy in various cohorts of traumatic brain injury (TBI) patients; therefore, we review the current evidences examining its utility for the same. The systematic review was done according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline including all human studies published in English language indexed with MEDLINE and Google Scholar since 2013 evaluating CS as a standalone or as an adjuvant procedure. The studies were graded according to the Oxford center for evidence-based medicine levels of evidence. Case reports were excluded from the analysis. A total of 107 articles were found by using the given search criteria. Finally, three oxford level 3 study and one level 4 study were included in the analysis. CS in combination with decompressive craniectomy was seen to confer mortality benefit and better outcome at discharge. It led to statistically significant improvement in clinical outcome at 6 months in the patients for whom it was performed as a primary procedure. CS is a promising procedure in TBI leading to survival benefit as well as better clinical outcome. But the level of evidence supporting its effectiveness is still weak owing to the methodological limitations and small sample size. A well-designed multicentric randomized controlled trial is needed to critically examine its role in TBI patients.
Keywords: cisternostomy; traumatic brain injury; CSF shift edema; Virchow-Robin spaces